Visir optic appliances designed for observation on the board of spaceships - Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The criteria for the efficiency definition of visir optic appliances for observation on the boards of spaceships are related to: the eye characteristics – the pupil diameter in dependence of the back-ground brightness, the visual sharpness and the utmost contrast; the photometric characteristics of the observed object and the background – their brightness and contrast; the optic characteristics of the visir optic appliance – magnification, vision field, entrance pupil diameter, light permeability, etc. Because the above mentioned class of appliances for cosmic research is used to observe distant ob-jects, when evaluating their efficiency, it is important to render an account of the atmospheric conditions. The visual distance of the distant objects depends on the photometric characteristics, on the object size and its shape. The presented in this research criteria for efficiency of the visir optic appliances used for observation on the boards of spaceships and also the coefficient which counts for the atmospheric influence allow evaluating the object visibility in the conditions of a natural landscape.